Low Doped n-type Localized Porous Silicon Made by Hole Injection from Back-side p+/n Junction for Power Switches Application. (18th September 2015) - Fèvre, Angélique; Menard, Samuel; Defforge, Thomas; Gautier, Gael
Abstract : The macropore morphology in low doped n-type silicon depending on hole supply technique is investigated. Electron-hole pair generation by illumination and hole injection through p + /n - back-side junction are compared in a highly concentrated HF electrolyte (30 wt. %). Then, the morphology similarities generated by the two techniques are verified towards anodization current density and electrolyte additives. Porous silicon layer is realized in low-doped n-type silicon as part of a device fabrication in industrial environment. Consequently, illumination technique induces implementation complexity. Then, porous silicon etching was investigated using hole injection from back-side p + /n - junction technique. In addition, implanted p + regions were incorporated in the low-doped n-type silicon at the anodic surface. We studied these regions in the capacity of masking layers. It was shown to be ineffective to prevent porous silicon formation as a mesoporous layer was observed after anodization.